The Shewanella algae strain YM8 produces volatiles with strong inhibition activity against Aspergillus pathogens and aflatoxins - Gong, An-Dong; Li, He-Ping; Shen, Lu; Zhang, Jing-Bo; Wu, Ai-Bo; He, Wei-Jie; Yuan, Qing-Song; He, Jing-De; Liao, Yu-Cai (Frontiers in Microbiology, 2015)
Aflatoxigenic Aspergillus fungi and associated aflatoxins are ubiquitous in the production and storage of food/feed commodities. Controlling these microbes is a challenge. In this study, the Shewanella algae strain YM8 was found to produce volatiles that have strong antifungal activity against Aspergillus pathogens. Gas chromatography-mass spectrometry profiling revealed 15 volatile organic compounds (VOCs) emitted from YM8, of which dimethyl trisulfide was the most abundant. We obtained authentic reference standards for six of the VOCs; these all significantly reduced mycelial growth and conidial germination in Aspergillus; dimethyl trisulfide and 2,4-bis(1,1-dimethylethyl)-phenol showed the strongest inhibitory activity. YM8 completely inhibited Aspergillus growth and aflatoxin biosynthesis in maize and peanut samples stored at different water activity levels, and scanning electron microscopy revealed severely damaged conidia and a complete lack of mycelium development and conidiogenesis. YM8 also completely inhibited the growth of eight other agronomically important species of phytopathogenic fungi: A. parasiticus, A. niger, Alternaria alternate, Botrytis cinerea, Fusarium graminearum, Fusarium oxysporum, Monilinia fructicola, and Sclerotinia sclerotiorum. This study demonstrates the susceptibility of Aspergillus and other fungi to VOCs from marine bacteria and indicates a new strategy for effectively controlling these pathogens and the associated mycotoxin production during storage and possibly in the field.